Premedication with midazolam in pediatric patients [Pediyatrik hastalarda midazolam premedikasyonunun induksiyon hemodinamisine etkileri] - (:unkn) unknown (My University, 1997)
Various doses of midazolam were used for premedication in pediatric patients. The results were evaluated in terms of sedation, hemodynamics and recovery. Fourty pediatric patients ranged in age from 4 to 7 years were included in the study. 10 of the patients were not given premedication and regarded as control group. The remaining 30 patients were divided into three groups each equal in member. Three study groups received midazolam diluted in 10 mL fruit juice in the doses of 0.25 mg/kg, 0.50 mg/kg, and 0.75 mg/kg respectively. Sedation status of the patients were 50 mg/kg, and recorded according to the sedation scale prior to the administration of midazolam and 5 minutes thereafter. Reactions to separation from mother and intravenous catheterization were noted. SpO2, respiratory rate, heart rate, mean systolic and diastolic blood pressure while breathing room air were recorded before and after premedication. Hemodynamic parameters were noted at intervals of 10 minutes during the operation and the first two hours postoperatively. Recovery time and side effects were also noted. Heart rate was found to be significantly decreased in III and IV groups 20 minutes after premedication when compared with the control group (p < 0.05). Sedation was significantly more prominent in groups III and IV when sedation scores were taken into consideration (p < 0.05). Reactions to separation were similar in study groups unrelated to the doses given and children were calm. In conclusion; premedication with 0.50 mg/kg oral midazolam is effective as 0.75 mg/kg and provides adequate sedation without side effects.
Keywords: midazolam; pediatric anaesthesia; premedication